2012
DOI: 10.4028/www.scientific.net/amr.461.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Color Shading Nets on Growth and Nutrient Uptake of Flowering Chinese Cabbage

Abstract: The effect of color shading-nets (red net, blue net and silver net) and ordinary black net on plant growth and nutrient uptake of flowering Chinese cabbage (Brassica campestris L. ssp. chinensis var. utilis Tsen et Lee) were studied, with no net shading as the control. The results indicated that, compared with the control, red net covering increased plant height, leaf area and stem diameter of flowering Chinese cabbage. Red and blue nets covering enhanced the above ground fresh weight, while the silver and bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Black and red shades increased PGIs of tea plants in 2018 and 2019 in this study, but there was no significant difference on PGIs between control and blue shade. Similar results were reported in other crops such as cabbage, snapdragon, marigold, and violet (12,38,39). Previous study showed that black shade nets absorbed all the ranges of light spectrum from 300 to 850 nm, blue shade nets had a high transmitting rate in the blue-green light spectrum range of 400 to 450 nm, while red shade nets had a high transmitting rate in orange-red light spectrum range of 590 to 850 nm (40).…”
Section: Discussionsupporting
confidence: 80%
“…Black and red shades increased PGIs of tea plants in 2018 and 2019 in this study, but there was no significant difference on PGIs between control and blue shade. Similar results were reported in other crops such as cabbage, snapdragon, marigold, and violet (12,38,39). Previous study showed that black shade nets absorbed all the ranges of light spectrum from 300 to 850 nm, blue shade nets had a high transmitting rate in the blue-green light spectrum range of 400 to 450 nm, while red shade nets had a high transmitting rate in orange-red light spectrum range of 590 to 850 nm (40).…”
Section: Discussionsupporting
confidence: 80%